Religious Moderation in the Era of Society 5.0: an Analysis of The Islamic Education Curriculum - Yuliansyah, Hafidz; Maemonah, (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze how the values of religious moderation are integrated into the curriculum at Madrasah Mu’allimin Yogyakarta and to evaluate their contribution to strengthening these values in the era of Society 5.0. Using a descriptive qualitative approach, data were collected through in-depth interviews with teachers and curriculum developers, as well as document analysis. Thematic analysis was used to identify patterns and relationships in the implementation of religious moderation within the curriculum. The results of the study show that Madrasah Mu’allimin Yogyakarta systematically integrates the values of religious moderation through a combination of national, distinctive, and international curricula. These values are instilled through intracurricular, cocurricular, and extracurricular activities, with an emphasis on tolerance, justice, appreciation of diversity, and character building. The curriculum is responsive to global challenges by utilizing participatory and project-based learning, supported by teachers who serve as role models and facilitators.